Five Strategies for Efficient and Effective Training of Japanese Resident Physicians Under the Japanese Work Style Reform - Nishizawa T; Ishizuka K; Miyagami T; Kondo K; Takai S; Fukushima K; Katto D; Nishizaki Y; Shimizu T (Advances in Medical Education and Practice)
Toshinori Nishizawa,1,2 Kosuke Ishizuka,3,4 Taiju Miyagami,5 Keita Kondo,6 Saya Takai,7 Kanako Fukushima,8 Daichi Katto,9 Yuji Nishizaki,10 Taro Shimizu11 1Department of General Internal Medicine, St. Luke’s International Hospital, Chuo-ku, Tokyo, Japan; 2Department of Global Health Promotion, Tokyo Medical and Dental University, Bunkyo-ku, Tokyo, Japan; 3Department of General Medicine, Yokohama City University School of Medicine, Yokohama-city, Kanagawa, Japan; 4Department of General Medicine, Yokohama City University Medical Center, Yokohama-city, Kanagawa, Japan; 5Department of General Medicine, Faculty of Medicine, Juntendo University, Bunkyo-ku, Tokyo, Japan; 6Community Based Medicine, Fujita Health University, Toyoake-city, Aichi, Japan; 7Department of General Internal Medicine, Iizuka Hospital, Iizuka-city, Fukuoka, Japan; 8Department of General Medicine, Itabashi Chuo Medical Center, Itabashi-ku, Tokyo, Japan; 9Department of General Medicine and Emergency Care, Toho University School of Medicine, Ota-ku, Tokyo, Japan; 10Division of Medical Education, Juntendo University School of Medicine, Bunkyo-ku, Tokyo, Japan; 11Department of Diagnostic and Generalist Medicine, Dokkyo Medical University, Shimotsuga-gun, Tochigi, JapanCorrespondence: Kosuke Ishizuka, Department of General Medicine, Yokohama City University School of Medicine, 3-9 Fukuura, Kanazawa-ku, Yokohama-city, Kanagawa pref, Japan, Tel +81-45-787-2800, Fax +81-45-350-2728, Email e103007c@yokohama-cu.ac.jpAbstract: Work-style reform in Japan, implemented in April 2019, aims to improve the well-being of physicians by regulating duty hours (DH). From 2024 to 2035, the DH for general physicians will be limited to 960 hours annually, while postgraduate year (PGY) 1 and 2 resident physicians may work up to 1860 hours to maintain sufficient training opportunities. However, studies indicate that excessive DH is associated with reduced sleep, worsened mental health, and increased risk of medical errors without significant improvement in clinical competence. This article proposes five strategies for balancing effective training and well-being among Japanese PGY1 and 2 residents within the framework of work-style reforms. Five key strategies are followed: 1) Flexible scheduling; 2) Task shifting and paperwork reduction; 3) Access to learning resources; 4) Feedback and mentorship; and 5) Workplace social capital and social support. By implementing these strategies, it is possible to enhance clinical residents’ health and educational experience, achieving a balance between work hours and training needs.Keywords: resident training, work-style reform, duty hours, mentorship, task shifting, medical education